Insulin Stimulates the Expression of the SHARP-1 Gene via Multiple Signaling Pathways - Takagi, K.; Asano, K.; Haneishi, A.; Ono, M.; Komatsu, Y.; Yamamoto, T.; Tanaka, T.; Ueno, H.; Ogawa, W.; Tomita, K.; Noguchi, T.; Yamada, K. (Hormone and Metabolic Research, 2014)
The rat enhancer of split- and hairy-related protein-1 (SHARP-1) is a basic helix-loop-helix transcription factor. An issue of whether SHARP-1 is an insulin-inducible transcription factor was examined. Insulin rapidly increased the level of SHARP-1 mRNA both in vivo and in vitro. Then, signaling pathways involved with the increase of SHARP-1 mRNA by insulin were determined in H4IIE rat hepatoma cells. Pretreatments with LY294002, wortmannin, and staurosporine completely blocked the induction effect, suggesting the involvement of both phosphoinositide 3-kinase (PI 3-K) and protein kinase C (PKC) pathways. In fact, overexpression of a dominant negative form of atypical protein kinase C lambda (aPKCλ) significantly decreased the induction of the SHARP-1 mRNA. In addition, inhibitors for the small GTPase Rac or Jun N-terminal kinase (JNK) also blocked the induction of SHARP-1 mRNA by insulin. Overexpression of a dominant negative form of Rac1 prevented the activation by insulin. Furthermore, actinomycin D and cycloheximide completely blocked the induction of SHARP-1 mRNA by insulin. Finally, when a SHARP-1 expression plasmid was transiently transfected with various reporter plasmids into H4IIE cells, the promoter activity of PEPCK reporter plasmid was specifically decreased. Thus, we conclude that insulin induces the SHARP-1 gene expression at the transcription level via a both PI 3-K/aPKCλ/JNK- and a PI 3-K/Rac/JNK-signaling pathway; protein synthesis is required for this induction; and that SHARP-1 is a potential repressor of the PEPCK gene expression.
Keywords: SHARP-1; insulin; transcription factor; liver; signal transduction